Effects of Exchange Rate and Inflation Uncertainty on Investment Opportunities of Companies listed in Tehran Stock Exchange - Elham Rahimi (Shahid Bahonar University of Kerman, 2016)
This study examined the effects of the real exchange rate and inflation uncertainty on the investment function of Tobin’s Q, in the period 2001-2010. To proceed, the data of 100 listed companies in the Tehran Stock Exchange were collected. The theoretical model were estimated by introducing the real exchange rate, and then, the inflation variable in the model. Exchange rate uncertainty was estimated by the generalized autoregressive conditional heteroscedasticity (GARCH) model, and the interactive correlations of the model variables were investigated by the GMM method. The results showed that the effects of the real exchange rate and inflation uncertainty variables in Tobin’s Q investment function are negative and significant. Also, the first lag of investment, cash flow, Tobin's Q and its lag variables have positive and significant effects on investment, and that the lagged cash flow, and the lagged real exchange rate uncertainty and the lagged inflation have negative and significant effects on investment.